Introduction to well logs and subsurface maps - Evenick, Jonathan (PennWell, 2018)
Subsurface mapping is a way to visualize and spatially characterize subsurface properties, and well logs are often the dataset used to generate and calibrate these maps. The correlation of basic geophysical logs rapidly enables oneself to begin to illustrate and understand the one-dimensional to 3D distribution of various properties. The second edition of Dr. Jonathan Evenick's book covers many types of basic well logs and subsurface maps. This book will help you quickly understand what many of these well logs are measuring and how they can be used to produce various subsurface maps. Three additional chapters and exercises have been included on spectral gamma ray logs, fault seal, geothermal energy, and source rock maps (unconventional resources).